The Immediate and Long-Term Impact of Preeclampsia on Offspring Vascular and Cardiac Physiology in the Preterm Infant - Annabelle L. Frost; Katie Suriano; Christina Y. L. Aye; Christina Y. L. Aye; Paul Leeson; Adam J. Lewandowski (Frontiers Media S.A., 2021)
Hypertensive disorders of pregnancy, including preeclampsia, affect nearly 10% of all pregnancies and are associated with significant long-term detrimental effects on both maternal and offspring cardiovascular health. Current management of preeclampsia involves timely delivery with the more severe form of disease requiring iatrogenic preterm birth. The effects on the maternal cardiovascular system have been studied extensively; however, less is known about the short- and long-term impacts on offspring cardiovascular health. There is a growing body of evidence suggesting that the offspring of pre-eclamptic pregnancies have an altered cardiac structure and function, along with a unique vascular physiology driven by lower endothelial function. Many of these changes can also be seen in those born preterm even in the absence of pregnancy hypertension. It is difficult to determine the relative contribution of pre-maturity and preeclampsia to the cardiovascular phenotype of those exposed to these pregnancy complications as they are, in many cases, inextricably linked. This review, therefore, focuses specifically on the evidence from clinical studies showing a negative cardiovascular impact of preeclampsia in preterm-born offspring, investigating phenotypic similarities and differences between offspring born preterm to normotensive vs. pre-eclamptic pregnancies. We explore the unique cardiac and vascular alterations in pre-eclamptic offspring born preterm, highlighting knowledge gaps, and potential areas of further research in the field.